A programmable pseudo-random binary sequence perturbation source for In Situ parameter estimation applications - Cornelissen, Karel Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1997.